Does Islamic finance enhance innovation capacity among Indonesian MSMEs? Evidence from a Multivariate Probit Approach - Sholeh, Maimun; Karunia, Anisah Novi; Pratista, Ardhana Reswari Hasna; Nurseto, Tejo (Universitas Islam Indonesia, 2026)
IntroductionInnovation capacity is essential for strengthening the competitiveness, productivity, and long-term sustainability of micro, small, and medium enterprises in developing economies. However, many Indonesian micro, small, and medium enterprises continue to face financing constraints that limit their ability to develop new products, improve business processes, reorganize internal capabilities, and adopt new marketing practices. Islamic finance offers a potentially relevant financing mechanism because it is based on Sharia-compliant principles, risk-sharing, asset-backed transactions, and real-sector orientation.ObjectivesThis study examines whether Islamic finance enhances innovation capacity among micro, small, and medium enterprises in Indonesia. Specifically, it analyzes the relationship between Islamic finance and four dimensions of innovation: product innovation, process innovation, organizational innovation, and marketing innovation.MethodThis study uses a quantitative approach based on primary survey data collected from micro, small, and medium enterprises in Yogyakarta and Central Java, Indonesia. The sample consists of Islamic finance users and non-users. Innovation capacity is measured through four binary indicators covering product, process, organizational, and marketing innovation. The data are analyzed using a multivariate probit model, which allows the four innovation outcomes to be estimated jointly while accounting for possible correlations among innovation decisions.ResultsThe findings show that Islamic finance is positively and significantly associated with product innovation, process innovation, and organizational innovation. The marginal effects indicate that Islamic finance users have a higher probability of introducing new or improved products, improving operational methods, and adopting organizational changes. However, Islamic finance is not significantly associated with marketing innovation, suggesting that financing alone may be insufficient to stimulate market-oriented changes such as branding, digital promotion, pricing, and distribution strategies.ImplicationsThe results imply that Islamic financial institutions should move beyond capital provision and support micro, small, and medium enterprises through mentoring, product development assistance, operational upgrading, halal ecosystem support, and digital capability building.Originality/NoveltyThis study contributes to the Islamic finance and innovation literature by analyzing multiple innovation dimensions simultaneously in the Indonesian micro, small, and medium enterprise context using a multivariate probit approach.